Effect of different litter materials on some behavioral patterns, growth performance, welfare indices, and carcass traits of Muscovy ducks - Eman Hefnawy; Ahmed Sabek; Eman Elgazzar; Saeed El-Laithy; Souad Ahmed (BMC Veterinary Research)
Abstract Background The current study was conducted to evaluate the effect of different litter materials on growth performance, some behavioral patterns, welfare indicators, and carcass traits in Muscovy ducks. A total of 84 healthy 2weeks old Muscovy ducklings were randomly allocated to 4 groups (3 replicates/ group; each replicate contains 7 birds) according to different litter materials. The first group was reared on wood shavings; the second was reared on sand; the third was reared on chopped rice straw; and the fourth one was reared on wheat straw. Growth performance parameters such as final body weight, body weight gain, feed intake, and feed conversion ratio were evaluated. Some behavioral patterns were recorded when the ducks were 3 weeks old using focal observation 3 days a week, twice per day. Foot pad dermatitis, feather condition score, hock burn, gait score, nostril cleanliness, and carcass traits were evaluated. Litter moisture content, water holding capacity, and microbiological characteristics of different litters were measured. Results The results showed that all growth performance parameters of Muscovy ducks were not significantly affected by different litter types (P > 0.05). Feeding and leg /wing stretch frequences were significantly higher in ducks reared on wood shavings and sand than other treatments. High pecking and low feather condition score were recorded in birds reared on sand more than other birds. The chopped rice straw group showed the lowest foot pad, gait, and hock burn scores. A little effect of litter types on carcass traits was recorded as only thymus and abdominal fat weights were influenced by different litter types (P ≤ 0.05). Sand litter had the lowest water holding capacity, moisture content, total bacterial and fungal counts when compared to other litter types. Conclusions In the Muscovy ducks’ sector, alternative bedding materials such as sand, wheat straw, and chopped rice can be used. Sand is the most hygienic litter to be used, as it has the lowest microbial load.